PENGARUH LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN (BAGIAN PRODUKSI MINYAK KELAPA SAWIT PT.MITRA UNGGUL PUSAKA SEGATI PELALAWAN RIAU) - Swandono Sinaga; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
PT. Mitra Unggul Pusaka Segati Pelalawan Riau engaged in the palm oil industry in Pelalawan Riau using raw materials of palm oil after it is produced into crude oil. PT.Mitra Unggul Pusaka have multiple departments. In this case, PT.Mitra Unggul Pusaka especially the oil production, which has 51 employees in 2015.The purpose of this study was to determine the influence of the work environment on employee productivity parts of palm oil production PT. Mitra Unggul Pusaka Segati Pelalawan Riau. This study uses descriptive quantitative correlation technique in which data were collected through questionnaires to 51 respondents. Then do the simple linear regression analysis of the data obtained.Results of research and hypothesis testing showed that there was a significant positive correlation between the work environment and productivity of employees part of palm oil production in PT. Partners Unggul Pusaka Segati Pelalawan Riau. Through coefficient determination test in this study proves that the work environment affects productivity of employees is influenced by other factors.Keywords: Work Environment, Employee Productivity